Improving Mathematics teaching and learning / Wan Zulkipli Wan Salleh and Wan Siti Esah Che Hussain - Wan Salleh, Wan Zulkipli; Che Hussain, Wan Siti Esah (UiTM Kedah, 2003)
This article gives suggestions to enhance the teaching and learning of mathematics. Mathematics is widely considered among the difficult and unappealing subject which has resulted in a syndrome of anxiety. By taking students' attitude and belief into consideration, this paper offers remedies to change their perceptions towards mathematics. It also highlights the students' responsibilities to improve their understanding of this subject. This paper also points out the importance of using different approaches to accommodate the diverse abilities among students and lastly, it discusses the significance of knowing how to read mathematics texts in improving the learning of mathematics.